2019
DOI: 10.3324/haematol.2019.222596
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative Gfi1b mutations cause moderate thrombocytopenia and an impaired stress thrombopoiesis associated with mild erythropoietic abnormalities in mice

Abstract: Dominant negative Gfi1b mutations cause moderate thrombocytopenia and an impaired stress thrombopoiesis associated with mild erythropoietic abnormalities in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…GFI1B mutations have been associated to a rare, dominant, congenital platelet disorder known as GFI1B-related thrombocytopenia (GFI1B-RT), caused by the presence of truncated GFI1B proteins with dominant-negative properties on megakaryocytopoiesis and thrombopoiesis [53]. The SNPs accounting for MPN predisposition are the rs621940 [11], the rs1633768, and rs524137 [13], of which the last two are located in a region of hematopoieticaccessible chromatin located around 12 kb downstream of GFI1B.…”
Section: Gfi1b and Chek2 Polymorphismsmentioning
confidence: 99%
“…GFI1B mutations have been associated to a rare, dominant, congenital platelet disorder known as GFI1B-related thrombocytopenia (GFI1B-RT), caused by the presence of truncated GFI1B proteins with dominant-negative properties on megakaryocytopoiesis and thrombopoiesis [53]. The SNPs accounting for MPN predisposition are the rs621940 [11], the rs1633768, and rs524137 [13], of which the last two are located in a region of hematopoieticaccessible chromatin located around 12 kb downstream of GFI1B.…”
Section: Gfi1b and Chek2 Polymorphismsmentioning
confidence: 99%
“…isoform that has all six zinc fingers, suggesting that the first two are not essential for the repressive function (Laurent et al, 2012;Beauchemin et al, 2019). However, it has been shown that the two isoforms play distinct roles in hematopoiesis, with the long isoform being important for megakaryocyte differentiation and maturation and the short isoform regulating erythropoiesis, indicating that zinc fingers 1 and 2 of GFI1B holds a megakaryocyte-specific function, probably by binding yet-to-be identified megakaryocyte factor(s) (Laurent et al, 2012;Polfus et al, 2016;Rabbolini et al, 2017;Schulze et al, 2017).…”
Section: Introduction Gfi1 and Gfi1b As Transcription Factorsmentioning
confidence: 99%
“…The long isoform 1 is required for megakaryocytic differentiation, while the shorter isoform induces proper erythropoiesis [94,141,142]. Mouse models with knockout or conditional knockout of Gfi1b revealed a severe phenotype [143], and thus, a novel Gfi1b dominant-negative mouse model was developed to obtain phenotypes similar to those found in humans [95]. Notably, patients with GFI1B-RT show hyperplasia of the MkPs and MKs in their bone marrow, which could also be observed in the mouse model.…”
Section: Gfi1bmentioning
confidence: 99%